Maternal Characteristics Are Associated with Child Dietary Diversity Score, in Golina District, Northeast Ethiopia: A Community-Based Cross-Sectional Study - Getahun Fentaw Mulaw; Fentaw Wassie Feleke; Seteamlak Adane Masresha (Journal of Nutrition and Metabolism)
Background. Dietary diversity is part of the set of indicators developed to assess infant and young child feeding practices. In developing countries, only a quarter of children met the required minimum dietary diversity. In Ethiopia, only 14% of children aged 6–23 months met the minimum dietary diversity score, with regional variation. Therefore, this study aimed to assess dietary diversity score and associated factors among children aged 6–23 months in Golina district, Afar region, Ethiopia. Method. A community-based cross-sectional study was conducted among 345 study participants from February 15 to March 30, 2017, in Golina district, Afar, Northeast Ethiopia. The study kebeles were selected randomly and the study subjects were selected using a cluster sampling technique. The child dietary diversity score was determined by the WHO child dietary diversity score scale, using a 24-hour dietary recall method, and data were collected using an interviewer-administered questionnaire. Multivariable logistic regression was used to identify predictor variables, and the level of significance was determined at P value <0.05. Result. This study revealed that children who met the required minimum dietary diversity score were 35.1% (95% CI, (30%–40%)). Children whose mothers have not attended formal education were 3.042 times (AOR = 3.042 95% CI: (1.312–7.052)) less likely to meet the minimum dietary diversity score than children whose mothers have attended secondary and above. Children whose mothers had normal BMI were 51.2% (AOR = 0.488, 95% CI: (0.259–918)) and 68.1% (AOR = 0.319, 95% CI: (0.119–0.855)) more likely to meet the minimum dietary diversity score than children whose mothers’ BMI was underweight and overweight, respectively. Conclusion. Maternal characteristics (educational status and nutrition status) were found to be associated with their child's dietary diversity score. This study also revealed that children who met the minimum dietary diversity score were few. Therefore, the increased emphasis on the importance of the education of girls (future mothers) and nutrition counseling for girls/women who currently have received little education on ways to improve the family and child dietary feeding practice is needed.